2020
DOI: 10.3390/cancers12041023
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of UTX/KDM6A Enriches Precursor Cell Populations in Urothelial Cell Cultures and Cell Lines

Abstract: The histone demethylase UTX (gene: KDM6A) directs cell and tissue differentiation during development. Deleterious mutations in KDM6A occur in many human cancers, most frequently in urothelial carcinoma. The consequences of these mutations are poorly understood; plausibly, they may disturb urothelial differentiation. We therefore investigated the effects of UTX siRNA-mediated knockdown in two in vitro models of urothelial differentiation; namely, primary cultures of urothelial epithelial cells treated with trog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Indeed, KDM6A mutations are associated with increased "stemness" in cancer and Kdm6a KO impairs mesoderm development in vivo largely through histone demethylase-independent mechanisms [20]. However, recent studies of Kdm6a KO models indicate that depletion of the enzyme does not block differentiation, and may even facilitate differentiation into neuroectoderm lineages [35,36]. Indeed, we only observed effects on germ layer marker genes after XCI has occurred and our KDM6A chromatin binding analyses suggest a direct effect of KDM6A on Xist expression during early XCI rather than an effect on differentiation itself.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, KDM6A mutations are associated with increased "stemness" in cancer and Kdm6a KO impairs mesoderm development in vivo largely through histone demethylase-independent mechanisms [20]. However, recent studies of Kdm6a KO models indicate that depletion of the enzyme does not block differentiation, and may even facilitate differentiation into neuroectoderm lineages [35,36]. Indeed, we only observed effects on germ layer marker genes after XCI has occurred and our KDM6A chromatin binding analyses suggest a direct effect of KDM6A on Xist expression during early XCI rather than an effect on differentiation itself.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, chromatin regulator mutations may enhance the self-renewal ability of urothelial precursor cells, favoring their clonal expansion. In support of this idea, we observed that knockdown of KDM6A in primary urothelial cell cultures and the normal urothelial cell line HBLAK, which comprise basal cells and KRT14-expressing stem cells, increased the proportion of cells expressing KRT14 [ 148 ]. Mutations inactivating KDM6A in normal urothelium may therefore augment the capacity of urothelial KRT14-expressing precursor cells for self-renewal, allowing them to gradually colonize the tissue at the expense of non-mutant urothelial precursors.…”
Section: Consequences Of Chromatin Regulator Alterations In Urothelial Carcinomamentioning
confidence: 91%
“…Accordingly, the KDM6A paralog KDM6B/JMJD3 is known to contribute to differentiation of cultured primary keratinocytes [ 147 ]. In primary urothelial and HBLAK cells, knockdown of KDM6A affected the balance between KRT14-positive stem cells and KRT5-positive basal cells but had only limited effects on further differentiation of luminal cells [ 148 ].…”
Section: Consequences Of Chromatin Regulator Alterations In Urothelial Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…KDM6A mutations are commonly lost in all stages and subtypes of urothelial cancer (UC), which is classified into non-muscle-invasive and muscle-invasive tumors (62)(63)(64)(65). Papillary UC is driven by loss of mutation of KDM6A in growth signaling pathway, especially activating FGFR3 and PIK3CA (119).…”
Section: Kdm6 In Cancermentioning
confidence: 99%